The "dekasseguis" o f Brazil went to Japan and there they are creating roots - Rossini, Rosa Ester (GEOUSP Espaço e Tempo (Online), 2003)
The current data toward migration are very fragmented, inconsistent and hard to be compared. About 250.000 Nikkeis from Brazil are calculated to be living in Japan. After the beginning of the 80s of 20th century this migration became evident. And almost 20 years living and working in the so called Sunrise country, the migrants whose were temporary at the beginning tend to be definitive. The new roots are evident and can be seen through the number of schools teaching Portuguese; of samba schools; the presence of the barbecue restaurants; the truck selling Brazilian food; video rental stores with movies spoken in Portuguese; of party and marriage with people from Japan or migrants from Brazil. In Japan, about 4 thousand children are born by year, whose parents are Nikkeis from Brazil.